Exploring Balanced Nutrition Knowledge and Nutritional Status among Adolescent Girls in Urban Areas - Enji Virginia Tampi; Yulianty Sanggelorang; Nova Hellen Kapantow (JURNAL BIOS LOGOS, 2024)
The nutritional status is indirectly influenced by the level of knowledge, which can affect an individual's attitudes and behaviors in food selection and ultimately impact their nutritional status. This study aims to analyze the relationship between balanced nutrition knowledge and the nutritional status of adolescent girls at State Senior High School (SSHS) 9 Manado. Employing an analytical survey method with a cross-sectional approach, the research was conducted from February to June 2023 at SSHS 9 Manado. The study sample comprised 100 adolescent girls selected through stratified random sampling. Nutritional status was assessed using a digital scale with a precision of 0.1 kg for weight measurement and a microtoise with a precision of 0.1 cm for height measurement. Additionally, a questionnaire consisting of 20 questions was administered to the adolescent girls to collect data on their nutrition knowledge. The research findings indicate that 49% of the respondents possessed sufficient nutrition knowledge, with 81% having a normal nutritional status. Statistical analysis using the Kruskal-Wallis test revealed no significant relationship between balanced nutrition knowledge and the nutritional status of adolescent girls, with a p-value of 0.610. Thus, it can be concluded that there is no significant association between balanced nutrition knowledge and the nutritional status of adolescent girls in this study.